PENGARUH BIOURINE SAPI TERHADAP SERAPAN NITROGEN DAN HASIL TANAMAN KACANG TANAH (Arachis hypogaea L.) PADA ENTISOLS SIDERA - Sari, Indah; Darman, Saiful (AGROTEKBIS, 2019)
This research aims to determine the effect of cow Biourine on Nitrogen (N) uptake of peanut plants (Arachis hypogaea L.) on Entisols of Sidera. The method used in this research was Randomized Block Design (RBD) with 7 doses and repeated three times so that there are 21 units of experiment. 7 doses of treatment were: B0 = No cow biourine (0 ml/plot), B1 = biourine cow dose of 583 l/ha (Equivalent to 210 ml/plot), B2 = biourine cow dose of 1166 l/ha (Equivalent to 420 ml/plot) B3 = biourine cattle dose of 1749 l/ha (Equivalent to 630 ml/plot), B4 = biourine cow dose 2332 l/ha (Equivalent to 840 ml/plot), B5 = biourine cow dose of 2915 l/ha (Equivalent to 1050 ml/plot), and B6 = biourine cow dose of 3498 l/ha (Equivalent to 1260 ml/plot). Research location in Sidera Village, Biromaru District, Sigi Regency. The cow biourine fertilizer used smells stinging and is brownish blackish coloured and liquid. Based on the results of the research showed that the highest N uptake level was achieved in the application of cow biourine with a dose of 3498 l/ha. The increased dosage of the fertilizer was not followed by an increase in soil pH but increased dose of cow biourine followed by increased C-organic, N-total, dry weight of plants, N concentration in plant tissue and number of plant pods and N uptake in peanut plants.